Molecular and biochemical characterization of the NS1 protein of non-cultured influenza B virus strains circulating in Singapore - Muhammad Raihan Jumat (2020)
In this study we compared the NS1 protein of Influenza B/Lee/40 and several non-cultured Influenza B virus clinical strains detected in Singapore. In B/Lee/40 virus-infected cells and in cells expressing the recombinant B/Lee/40 NS1 protein a full-length 35 kDa NS1 protein and a 23 kDa NS1 protein species (p23) were detected. Mutational analysis of the NS1 gene indicated that p23 was generated by a novel cleavage event within the linker domain between an aspartic acid and proline at amino acid residues at positions 92 and 93 respectively (DP92-93), and that p23 contained the first 92 amino acids of the NS1 protein. Sequence analysis of the Singapore strains indicated the presence of either DP92-93 or NP92-93 in the NS1 protein, but protein expression analysis showed that p23 was only detected in NS1 proteins with DP92-93.. An additional adjacent proline residue at position 94 (P94) was present in some strains and correlated with increased p23 levels, suggesting that P94 has a synergistic effect on the cleavage of the NS1 protein. The first 145 amino acids of the NS1 protein are required for inhibition of ISG15-mediated ubiquitination, and our analysis showed that Influenza B viruses circulating in Singapore with DP92-93 expressed truncated NS1 proteins and may differ in their capacity to inhibit ISG15 activity. Thus, DP92-93 in the NS1 protein may confer a disadvantage to Influenza B viruses circulating in the human population and interestingly the low frequency of DP92-93detection in the NS1 protein since 2004 is consistent with this suggestion.